Hubungan Antara Kualitas Pribadi Guru BK dengan Kepuasan Siswa dalam Mengikuti Bimbingan Klasikal SMA Negeri Se Kabupaten Klaten Timur - Widya Sholikhah; Muslikah Muslikah (Departement of Mathematics Education, 2023)
He relationship between the personal qualities of the guidance and counseling teacher greatly influences student satisfaction in following classical guidance because each student has different causes and levels of satisfaction. This study aims to determine the relationship between the personal qualities of counseling teachers and student satisfaction in following classical guidance. This study uses a quantitative approach with a correlational design. The population in this study were all 11th grade students in Klaten district, totaling 919 students. The sampling technique used in this study was using a proportional random sampling technique with a total of 251 students. The measuring instrument used in this study uses two scales, namely the scale of student satisfaction in participating in classical guidance services and the personal quality scale of the counseling teacher. The data analysis technique used in testing this hypothesis is by using product moment correlation analysis. In this study, the results showed that the results of the product moment correlation analysis showed (r_xy = 0.720 Sig = 0.000) which means that there is a positive and significant relationship between the personal quality variables of guidance counselors and student satisfaction in following classical guidance. This means that the personal quality of the counseling teacher is good, so student satisfaction will also increase and vice versa.